Privacy of Crowdsourcing Educational Platforms in the Light of New EU Regulations Authors - Zdravkova, Katerina (CEUR-WS Workshop Proceedings, 2019)
Many crowdsourcing systems enable an anonymous access and opportunity to namelessly contribute self-generated content without providing any personal data. However, Internet browsers collect metadata on a large scale, including learning management systems (LMS), which collect and store many identity and contact data. System administrators and the teachers responsible for the courses can access them at any time. Interactive activities embedded in the LMS can reveal sensitive data, such as religious beliefs, political views, health, sexual orientation, race, or membership to organizations. They are visible to all the enrolled students.Educational organizations who are hosting LMS, also collect a lot of data that is usually transferred to third countries, but also transmitted to third parties, including university researchers or outside companies, often even governments. This paper examines the challenges of a prospective crowdsourcing platform intended for education, which must be taken into consideration by design. It presents examples of violated privacy in education, the student protection regulations, and the privacy concerns of learning management systems. The compliance of the most popular LMSs, MOOCs and crowdsourcing systems with GDPR are examined and compared. The paper concludes with the privacy policy guidelines of the prospective crowdsourcing educational platform in the light of GDPR.
Keywords: Crowdsourcing, GDPR, LMS, rights of data subject